2020
DOI: 10.1039/d0ra08003a
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein coupled receptors: structure and function in drug discovery

Abstract: The G-protein coupled receptors (GPCRs) superfamily comprise similar proteins arranged into families or classes thus making it one of the largest in the mammalian genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 89 publications
1
29
0
Order By: Relevance
“…In contrast to multi-pass (integral) membrane proteins, where considerable work has been performed, in particular the GPCR class of membrane proteins e.g., [885][886][887][888][889][890][891][892][893][894][895][896][897][898][899] (for review see references: [31,[900][901][902][903]), that are a very hot topic, peripheral and bitopic (single pass) membrane proteins, which constitute 43-45% of transmembrane proteins [883], are underrepresented in MD simulation studies.…”
Section: Other Effects On Lipid Layers-pulmonary Surfactants and Indirect Effect On Membrane Proteinsmentioning
confidence: 99%
“…In contrast to multi-pass (integral) membrane proteins, where considerable work has been performed, in particular the GPCR class of membrane proteins e.g., [885][886][887][888][889][890][891][892][893][894][895][896][897][898][899] (for review see references: [31,[900][901][902][903]), that are a very hot topic, peripheral and bitopic (single pass) membrane proteins, which constitute 43-45% of transmembrane proteins [883], are underrepresented in MD simulation studies.…”
Section: Other Effects On Lipid Layers-pulmonary Surfactants and Indirect Effect On Membrane Proteinsmentioning
confidence: 99%
“…In line with these results and in agreement with the anti-inflammatory and anti-oxidative actions of GTE, we found that P2Y12R-positive, neuroprotective M2, microglia significantly increases after chronic intake of GTE and translocate P2Y12R to the nucleus. The nuclear expression of this purinergic receptor in microglia following GTE supplementation is difficult to conciliate with the role of a G-protein coupled receptor such as P2Y12R, considered as a cell-surface receptor whose primary function is to transduce extracellular stimuli into intracellular signals [ 144 ]. Nevertheless, our results are in concordance with previous data on microglial activation in gliomas, in which it has been reported a shift from cytoplasmic to nuclear expression of P2Y12R linked to the acquisition of the M2 phenotype [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a structural perspective, all GPCRs display the same architecture—seven transmembrane alpha helices (TMs) connected by three intracellular and three extracellular loops (ICL1-3, ECL1-3). N-termini and C-termini, which the majority of GPCRs possess, can vary in length and in regulatory roles they play in GPCR signaling ( Coleman et al, 2017 ; Odoemelam et al, 2020 ).…”
Section: G Protein-coupled Receptor Related Structural Elements Of Gp...mentioning
confidence: 99%